KEARIFAN LOKAL CERITA RAKYAT MELAYU LANGKAT - Rosliani Nfn; Hasan Al Banna; Melani Rahmi Siagian (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Malay culture is regarded as a globalized culture. Folklore is part of Malay culture. Langkat Malay community must understand and feel has a wealth of literary folklore mainly so that their lives are not uprooted from their own culture. Langkat Malay community has a very rich cultural potential, one of which is folklore. Folklore contains noble cultural values and local wisdom that can make its owner into a modern society that is characterized by Indonesia. To unravel this case used qualitative methods to the theory of narrative structure and functional. The results showed that the structure of gender relations, men dominate women and one brave woman story rights. Then the local wisdom that can be taken is to be fair, thoughtful, honest, caring for the environment, and responsible can make life better. Especially this attitude must be owned by a leader.